Molasses : dampak negatif pada ruminansia - yanuartono - yanuartono; Alfira Nururrozi; Soedarmanto Indarjulianto; Slamet Raharjo (Faculty of Animal Science, Universitas Brawijaya, 2017)
ABSTRACTMolasses is a by-product or end product of sugar cane (Saccharum officcinarum L.) or sugar-beet (Beta vulgaris L. var. Conditiva) resulting from the manufacture of raw or refined sugar and consisting of structural sugars, hemicelluloses and minerals. It is mainly used to improve appetite of animals or add extra energy when prices of molasses are lower than that of other energy sources. Molasses can be a key ingredient for cost effective management of feeds and pastures. Supplementing poor quality feeds with molasses will increase feed intake and improve palatability. However, molasses can be toxic if fed at ad libitum or free choice, therefore, it is recommended that molasses should be supplemented in a restrictive form. These molasses poisoning papers and the negative impacts arose from long-standing studies because the poisoning is now rare. However, although this time is rare but did not close the possibility will appear again, Especially if given in an uncontrolled amount. Thus, this paper aims to remind users of molasses in the livestock industry to be wiser in their use. Key words: Key words: molasses, sugar cane, palatability, toxic